2021
DOI: 10.1186/s12909-021-02622-x
|View full text |Cite
|
Sign up to set email alerts
|

Career choice and influential factors among medical students majoring in psychiatry in China

Abstract: Background The undergraduate program of psychiatry has been widely established in recent years to improve the education and recruitment of psychiatrists in China. We aim to investigate the career choice of medical students majoring in psychiatry in China and the influential factors. Method This multicenter study was conducted in 26 medical schools in China from May to October of 2019. Participants included 4610 medical students majoring in psychiat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Previous studies have mostly focused on in uencing factors about the specialty or subspecialty choice for medical students [17][18][19]. An imbalance in the supply of doctors in different specialties and subspecialties is vital to the healthcare industry.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have mostly focused on in uencing factors about the specialty or subspecialty choice for medical students [17][18][19]. An imbalance in the supply of doctors in different specialties and subspecialties is vital to the healthcare industry.…”
Section: Resultsmentioning
confidence: 99%
“…Based on data released by the National Health Commission (2021) in January 2021, for every 100,000 persons in the population, there were only 1.49 psychiatrists (including assistant practitioners) in 2014 and it significantly increased to 3.43 psychiatrists in 2019. Although the number of personnel has been improved, but compared with 13.06 psychiatrists in high income countries, the percentage was still very low (Y. Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of personnel has been improved, but compared with 13.06 psychiatrists in high income countries, the percentage was still very low (Y. Zhang et al, 2021). The perfection of the rehabilitation system needs a long-term process.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study demonstrate that family (parents) has a significant relationship with career decision making (t=3.828), (=0.197), and (P=0.000). (Zhang et al, 2021) and (Owusu et al, 2021), both found similar parents want their children to have a nice life and earn a good salary, so they encourage and drive them to choose occupations. The study also found that peer groups have no significant link with career decision-making, as seen by the findings (t=0.906), (=0.052), and (P=0.365).…”
Section: Discussion Of the Findingsmentioning
confidence: 99%
“…Semistructural interviews with 23 postgraduate students were conducted by (Adefulu, Farinloye, & Mogaji, 2020) on study on factors impacting postgraduate students' university choice in Nigeria, Parents have a statistical significant influence on their children's professional choices, according to research. (Zhang et al, 2021), observed that family suggestions (OR = 1.25, 95 percent CI = 1.08-1.46) correlated positively with students' choice of psychiatry as a career in a study on career choice and influential factors among Chinese medical students specialising in psychiatry. This shows that family has significant relationship with career decision of psychiatric students.…”
Section: Family Factor and Career Decision Makingmentioning
confidence: 99%